Large-diameter ternary positive electrode precursor with inhibited spontaneous cracking, and preparation method and application thereof

CN122977462APending Publication Date: 2026-10-27YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611108822.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有改进多集中于抑制外部碰撞开裂,对自发开裂问题缺乏有效手段

Benefits of technology

1.本发明通过在共沉淀反应中期,在颗粒晶界处原位构建非晶态应力滑移层,并结合分段原位应力退火工艺,实现了对大粒径三元前驱体内部残余应力的有效释放与缓冲。采用本发明方法制备的前驱体,自发开裂率可控制在1%-6%之间,而传统工艺的开裂率高达15.2%,开裂率降幅显著。本发明从根源上解决了大粒径前驱体因内部结晶度差异导致的应力集中问题,有力保障了产品结构的完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977462A_ABST
    Figure CN122977462A_ABST
Patent Text Reader

Abstract

The application discloses a large-particle-size ternary positive electrode precursor capable of inhibiting spontaneous cracking, and a preparation method and application thereof, and belongs to the technical field of lithium battery positive electrode materials. The application first completes the basic growth of the precursor particles through a coprecipitation reaction of a nickel-cobalt-manganese mixed salt, a precipitant and a complexing agent, then forms an in-situ coating stress release structure by pulse adding of a grain boundary slow-release layer additive to buffer the grain boundary growth stress, further adopts a segmented pause feeding annealing process to release the accumulated stress in the particles step by step, and effectively solves the defects of easy cracking and existing microcracks of the large-particle-size precursor. Finally, the finished product is obtained through aging, washing, drying and other post-treatments. Through the synergistic effect of coating modification and segmented annealing, the application completely improves the stress concentration problem of the large-particle-size particles, the product structure is complete and the consistency is good, the structural stability of the positive electrode material and the cycle life of the battery can be effectively improved, the process is simple and controllable, and is suitable for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery cathode material technology, and more specifically, to a large-particle-size ternary cathode precursor that inhibits spontaneous cracking, its preparation method, and its application. Background Technology

[0002] LiNi ternary cathode material x Co y Mn 1-x-y O2 (NCM) has become one of the mainstream cathode materials for lithium-ion batteries due to its high specific capacity and good cycle performance. Its electrochemical performance largely depends on the precursor Ni. x Co y Mn 1-x-y The quality of (OH)₂. Currently, the main industrial method for preparing ternary precursors is the co-precipitation method. This involves adding a nickel-cobalt-manganese mixed salt solution along with a precipitant and a complexing agent in a continuous stirred reactor under alkaline conditions. The resulting hydroxide precipitate is then aged, washed, and dried to obtain the final product. This process is continuous, has high capacity, and produces stable product quality. By controlling parameters such as pH, ammonia concentration, temperature, and stirring speed, particle size, sphericity, and tap density can be effectively controlled. As the reaction time increases, the particles gradually grow; when the D50 reaches over 10 μm, a large-particle-size product with high tap density can be obtained, which is beneficial for improving the volumetric energy density of the cathode material.

[0003] However, production practice shows that large-particle-size precursors (D50 exceeding 10 μm) are prone to cracking, severely affecting product yield. The causes of cracking include both external and internal factors: external factors include intensified collisions between particles and between particles and the agitator, resulting in high shear forces acting on the particle surface and causing cracks. Existing technologies have attempted to mitigate this by adding anti-cracking agents or reducing the rotation speed in later stages. Internal factors involve a longer reaction time in the particle core region, resulting in coarse and dense primary grains, while the outer shell region has a shorter sedimentation time, leading to finer primary grains and lower crystallinity. This difference in crystallinity accumulates within the particles, creating significant residual tensile stress. When this stress exceeds the grain boundary bonding strength, cracks nucleate and propagate along the grain boundaries, i.e., "spontaneous cracking." Current improvements mainly focus on suppressing external collision cracking, lacking effective methods for addressing spontaneous cracking.

[0004] Therefore, there is an urgent need to develop a preparation method that starts from internal stress regulation to effectively suppress the spontaneous cracking of large-particle-size ternary precursors, so as to ensure the integrity of particle structure and batch consistency. This has important industrial value for improving the cycle stability and safety of cathode materials.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide a large-particle-size ternary cathode precursor that suppresses spontaneous cracking, its preparation method, and its application.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a large-particle-size ternary cathode precursor that inhibits spontaneous cracking, comprising the following steps: mixing a nickel-cobalt-manganese mixed salt solution, a precipitant, and a complexing agent to carry out a co-precipitation reaction; when the particle size D50 of the particles in the reaction system grows to 60%-70% of the target particle size D, adding a grain boundary slow-release layer additive to the system in a pulsed manner to perform in-situ coating modification on the particle surface; continuing the reaction until the particle size D50 of the coated particles grows to 70%-80% of the target particle size D, stopping the feeding, performing a first annealing, and continuing the feeding after annealing; continuing the reaction until the particle size D50 grows to 90%-95% of the target particle size D, stopping the feeding, performing a second annealing, and continuing the feeding after annealing; continuing the reaction until the particle size reaches the target particle size D, aging, washing, drying, and post-treatment of the obtained slurry to obtain the ternary cathode precursor.

[0008] In an optional embodiment, the total metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 1.5 mol / L - 2.5 mol / L; And / or, the precipitant is a sodium hydroxide solution with a concentration of 4 mol / L - 12 mol / L; And / or, the complexing agent is an aqueous ammonia solution with a concentration of 4 mol / L - 12 mol / L; And / or, the target particle size D of the ternary cathode precursor is 10 μm - 20 μm.

[0009] In an optional embodiment, the coprecipitation reaction includes at least one of the following features: Feature 1: The coprecipitation reaction temperature is 40 ℃-80 ℃; Feature 2: The pH value of the coprecipitation reaction system is 9.5-12.5; Feature 3: The concentration of free ammonia in the coprecipitation reaction system is 0.1 mol / L - 0.5 mol / L; Feature 4: The stirring speed is controlled at 100 rpm - 1000 rpm during the coprecipitation reaction.

[0010] In an optional embodiment, the grain boundary slow-release layer additive is selected from at least one of silicate additives or phosphate additives. And / or, the pulsed addition method is as follows: each injection of the grain boundary slow-release layer additive solution is 10 mL / m 3 -20 mL / m3 Inject 3-5 times consecutively at 10-15 minute intervals.

[0011] In an optional embodiment, the grain boundary slow-release layer additive is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, tetraethyl orthosilicate, and sodium silicate.

[0012] In an optional embodiment, the concentration of the phosphate additive solution is 0.2 g / L-1.0 g / L, and the pH value is 7.0-7.5; And / or, the silicate additive is a silica sol with a particle size <5 nm, or a silicate solution with a concentration of 0.2 g / L-1.0 g / L.

[0013] In an optional embodiment, the annealing process takes 10-60 minutes; And / or, the reaction during the annealing process includes at least one of the following characteristics: Feature 1: The stirring speed during the reaction is 40 rpm - 800 rpm; Feature 2: The pH value of the reaction system is 8.7-12.5; Feature 3: The concentration of free ammonia in the reaction system is 0 mol / L-0.5 mol / L.

[0014] Secondly, the present invention provides a ternary cathode precursor obtained by the above preparation method. The ternary cathode precursor is a secondary spherical particle of nickel cobalt manganese hydroxide. The secondary spherical particle is formed by the aggregation of primary particles. The grain boundary gaps between the primary particles are in situ coated with a grain boundary slow-release layer. The grain boundary slow-release layer is an amorphous or weakly crystalline stress slip layer with a thickness of 2 nm-10 nm.

[0015] Thirdly, the present invention provides a cathode material obtained by sintering a ternary cathode precursor mixed with a lithium source obtained by the above preparation method.

[0016] In an optional embodiment, the molar ratio of metal ions to lithium source in the ternary cathode precursor is 1:(1.00-1.08); the sintering process is as follows: pre-sintering at 400℃-600℃ for 4h-6h by heating at 2℃ / min-5℃ / min, then heating to 700℃-850℃ and holding for 10h-15h, and then cooling to room temperature in the furnace.

[0017] The present invention has the following beneficial effects: 1. This invention achieves effective release and buffering of residual stress within large-particle-size ternary precursors by constructing an amorphous stress-slip layer in situ at grain boundaries during the mid-stage of the co-precipitation reaction, combined with a segmented in-situ stress annealing process. Precursors prepared using this method exhibit a spontaneous cracking rate controlled between 1% and 6%, while the cracking rate of traditional processes reaches as high as 15.2%, demonstrating a significant reduction in cracking rate. This invention fundamentally solves the stress concentration problem caused by internal crystallinity differences in large-particle-size precursors, effectively ensuring the integrity of the product structure.

[0018] 2. This invention utilizes the spontaneous enrichment characteristics of additives at grain boundaries, achieving a significant stress buffering effect with minimal additive amounts, thus avoiding the impact of large amounts of impurities on material purity. Specifically, phosphate additives can be converted into beneficial Li3PO4 grain boundary phases during subsequent sintering, with residual amounts of only 10-100 ppm. This not only does not reduce material purity but also helps improve grain boundary toughness. Silicate additives can be completely volatilized with the assistance of water vapor (residual <10 ppm), meeting the stringent impurity content requirements of different customers and exhibiting good formulation adaptability.

[0019] 3. The large-particle-size ternary precursor prepared by the method of this invention, after lithium mixing and sintering, results in a cathode material with significantly improved capacity retention compared to traditional precursors, and effectively improved cycle stability and safety. Furthermore, the process of this invention is highly adaptable, covering various product specifications, simple to operate, and highly compatible with existing industrial co-precipitation production lines. It requires no additional complex equipment and is easy to commercialize and apply. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a process flow diagram of an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of the precursor particles in Example 1 of this invention; Figure 3 This is a scanning electron microscope image of the precursor particles in Comparative Example 1 of this invention. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0023] The inventors have discovered that when secondary particles of ternary precursors grow to a D50 ≥ 10 μm, spontaneous cracks still appear on the particle surface and inside the particle even without external mechanical shear force, under static aging or low-stirring conditions. These cracks radiate outwards from the particle center, and in severe cases, the entire particle breaks into 2-5 fragments along the grain boundaries. SEM cross-sectional observation shows that these cracks mainly propagate along the grain boundaries between primary particles. The cause is that as the particle size increases, there are significant differences in crystallinity and densification among primary particles at different depths within the precursor. This structural inhomogeneity accumulates within the particles, forming substantial residual stress. Once this stress exceeds the grain boundary bonding strength, cracks spontaneously nucleate and propagate. Compared to impact cracking caused by external shear force, this type of "spontaneous cracking" driven by internal stress is more difficult to control and is almost unavoidable in the production of large-particle-size precursors ≥ 10 μm. Currently, there is a lack of effective solutions to this problem in the industry. In view of this, the present invention proposes the following technical solution in order to significantly suppress spontaneous cracking of large-particle-size ternary precursors from the perspective of internal stress regulation.

[0024] The first aspect of this invention proposes a method for preparing a large-particle-size ternary cathode precursor that suppresses spontaneous cracking, the process flow diagram of which is shown below. Figure 1 As shown, it includes the following steps: S1. Mix the nickel-cobalt-manganese mixed salt solution, precipitant, and complexing agent to carry out a co-precipitation reaction.

[0025] The mixed metal salt solution is prepared by combining nickel salt, cobalt salt, and manganese salt according to the pre-defined molar ratio of nickel, cobalt, and manganese in the molecular formula of the ternary cathode material. The nickel-cobalt-manganese mixed salt solution is selected from sulfate or nitrate solutions, and its total metal ion concentration is 1.5 mol / L - 2.5 mol / L, such as 1.5 mol / L, 1.7 mol / L, 1.9 mol / L, 2.1 mol / L, 2.3 mol / L, or 2.5 mol / L, etc. Preferably, the precipitant is a sodium hydroxide solution with a concentration of 4 mol / L - 12 mol / L, such as 4 mol / L, 6 mol / L, 8 mol / L, 10 mol / L or 12 mol / L, or any other value within the range of 4 mol / L - 12 mol / L; Preferably, the complexing agent is an ammonia solution with a concentration of 4 mol / L to 12 mol / L, such as 4 mol / L, 6 mol / L, 8 mol / L, 10 mol / L, or 12 mol / L, or any other value within the range of 4 mol / L to 12 mol / L.

[0026] In a preferred embodiment of this application, the target particle size D of the ternary cathode precursor is 10μm-20μm, such as 10μm, 12μm, 14μm, 16μm, 18μm or 20μm, or any other value in the range of 10μm-20μm.

[0027] In this application, the temperature of the coprecipitation reaction is 40 ℃-80 ℃, such as 40 ℃, 50 ℃, 60 ℃, 70 ℃ or 80 ℃, or any other value within the range of 40 ℃-80 ℃.

[0028] The pH value of the coprecipitation reaction system is 9.5-12.5, such as 9.5, 10.0, 10.5, 11.0, 11.5, 12.0 or 12.5, or any other value within the range of 9.5-12.5.

[0029] The free ammonia concentration in the coprecipitation reaction system is 0.1 mol / L - 0.5 mol / L, such as 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L, or any other value within the range of 0.1 mol / L - 0.5 mol / L.

[0030] The coprecipitation reaction described above is preferably carried out under stirring conditions, for example, at a stirring speed of 100 rpm. 1000rpm, such as 100rpm, 200rpm, 500rpm, 800rpm, or 1000rpm, can also be 100rpm. Any other value within the 1000rpm range.

[0031] S2. When the particle size D50 of the particles in the reaction system grows to 60%-70% of the target particle size D, the grain boundary slow-release layer additive is added to the system in a pulse manner to perform in-situ coating modification on the particle surface.

[0032] In some preferred embodiments, the grain boundary slow-release layer additive is selected from at least one of silicate additives or phosphate additives; preferably at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, tetraethyl orthosilicate, and sodium silicate.

[0033] It should be noted that the grain boundary slow-release layer additive is added in multiple stages, and the type of additive added each time can be different.

[0034] Specifically, the preparation method of the grain boundary sustained-release layer solution includes: For phosphate additives, dissolve them in deionized water to prepare a solution of 0.2-1.0 g / L, and adjust the pH to 7.0-7.5 with ammonia. For silicate additives, premix tetraethyl orthosilicate and anhydrous ethanol at a volume ratio of 1:3, then slowly add deionized water to hydrolyze it to form SiO2 sol (particle size <5nm), or directly dissolve sodium silicate in water to prepare a solution of 0.2-1.0 g / L.

[0035] In a preferred embodiment of this application, the pulsed addition method is as follows: based on the volume of the reaction system slurry, 10 mL / m of the grain boundary slow-release layer additive solution is injected each time. 3 -20 mL / m 3 Inject 3-5 times consecutively at 10-15 minute intervals.

[0036] For reference, the amount of grain boundary slow-release layer additive solution added can be 10 mL / m 3 12 mL / m 3 14 mL / m 3 16 mL / m 3 18 mL / m 3 Or 20 mL / m 3 The interval can be 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, etc.; and it can be injected 3, 4 or 5 times consecutively.

[0037] After the grain boundary slow-release layer additive enters the reaction system, it spontaneously accumulates in the grain boundary gaps between primary particles, undergoing hydrogen bonding or coordination with surface M-OH groups to form an amorphous or weakly crystalline stress slip layer with a thickness of 2-10 nm. This slip layer can undergo micron-level slip deformation when the residual stress inside the particles exceeds a threshold, dissipating strain energy and effectively inhibiting crack initiation and propagation along grain boundaries.

[0038] S3. Continue the reaction until the particle size D50 of the coated particles grows to 70%-80% of the target particle size D, then stop feeding and perform the first annealing. After the annealing is completed, continue feeding.

[0039] S4. Continue the reaction until the particle size D50 grows to 90%-95% of the target particle size D. Stop feeding and perform a second annealing. After the annealing is completed, continue feeding.

[0040] During the feeding pause, the stirring speed is reduced to 40%-80% of the reaction speed, and the pH value of the reaction system is lowered by 0-0.8, the free ammonia concentration is lowered by 0-0.2 mol / L, and an inert gas (nitrogen or argon) is introduced into the reactor to reduce the dissolved oxygen concentration in the system and suppress the slight oxidation that may occur on the surface of the high-nickel system during annealing. The holding time for the first annealing treatment and the second annealing treatment are independent and are both in the range of 10 min-60 min.

[0041] Specifically, during the feed pause, the stirring speed of the reaction is 40 rpm - 800 rpm, which can be 40 rpm, 100 rpm, 200 rpm, 400 rpm, or 800 rpm, or any other value within the range of 40 rpm - 800 rpm; the pH value of the reaction system is 8.7 - 12.5, which can be 8.7, 9.3, 9.9, 10.5, 11.0, 11.5, 12.0, or 12.5, or any other value within the range of 8.7 - 12.5; the free ammonia concentration in the reaction system is 0 mol / L - 0.5 mol / L, which can be 0 mol / L, 0.10 mol / L, 0.20 mol / L, 0.30 mol / L, 0.40 mol / L, or 0.50 mol / L, or any other value within the range of 0 mol / L - 0.5 mol / L.

[0042] Under these low supersaturation conditions, the fine primary grains on the particle surface undergo selective dissolution. At the same time, metal ions in the solution are deposited on the surface of the highly crystalline grains under low supersaturation. Through the dissolution-redeposition mechanism, the size and crystallinity of the primary grains inside the particle tend to be uniform, thereby eliminating the residual stress caused by the difference in crystallinity between the core and the shell.

[0043] S5. Continue the reaction until the particle size reaches the target particle size D. Then, age, wash, dry, mix, sieve, demagnetize, and package the resulting slurry to obtain the ternary cathode precursor.

[0044] In some embodiments, the slurry is first aged in an aging kettle (the aging time can be 0-120h). After aging, it is filtered, and the filter cake is added with a certain concentration (such as 0.2-3mol / L) of dilute alkali (such as sodium carbonate or sodium hydroxide) for pulping. Then it is filtered and washed until the pH value of the filtrate is less than 9. After drying, sieving, demagnetizing and packaging, the ternary cathode precursor material can be obtained.

[0045] It should be noted that in this application, the precursor preparation process is carried out under a protective atmosphere, such as a nitrogen atmosphere or an argon atmosphere, to ensure that the slurry is not oxidized.

[0046] Secondly, the present invention provides a ternary cathode precursor obtained by the above preparation method. The ternary cathode precursor is a secondary spherical particle of nickel cobalt manganese hydroxide. The secondary spherical particle is formed by the aggregation of primary particles. The grain boundary gaps between the primary particles are in situ coated with a grain boundary slow-release layer. The grain boundary slow-release layer is an amorphous or weakly crystalline stress slip layer with a thickness of 2 nm-10 nm.

[0047] Thirdly, the present invention provides a cathode material, which is obtained by sintering a ternary precursor cathode material mixed with a lithium source obtained by the above preparation method.

[0048] The molar ratio of metal ions to lithium source in the ternary cathode precursor can be any value in the range of 1:(1.00-1.08), such as 1:1.00, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, or 1:1.08.

[0049] Specifically, the sintering process is as follows: the temperature is increased to 400℃-600℃ at a rate of 2℃ / min - 5℃ / min for 4h-6h for pre-firing, then the temperature is increased to 700℃-850℃ and held for 10h-15h, and then cooled to room temperature with the furnace.

[0050] During sintering, the grain boundary slow-release layer additives undergo the following phase evolution: For phosphate additives, a metal phosphate salt mesophase is first formed in the 200-350℃ temperature range, and then reacts with the lithium source in the 400-600℃ temperature range to generate Li3PO4 nanoparticles, which are uniformly dispersed at the grain boundaries of the primary particles. The residual Li3PO4 content is approximately 10-100 ppm. This phase, as a solid electrolyte, can enhance the grain boundary bonding force and effectively inhibit the propagation of microcracks during electrochemical cycling. For silicate additives, amorphous SiO2 or lithium silicate is first generated in the pre-sintering stage. Subsequently, 2%-5% by volume of water vapor is introduced in the pre-sintering section. SiO2 reacts with water vapor to generate volatile Si(OH)4, thereby being completely removed. The final residual amount can be controlled below 10 ppm. Those skilled in the art can flexibly select the appropriate additive system according to the purity requirements and performance requirements of the target product to obtain the optimal effect that balances stress release and phase control.

[0051] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0052] Example 1 This embodiment provides a method for preparing an NCM811 ternary cathode precursor with a D50 of 15 μm using an ammonium dihydrogen phosphate system, including the following steps: Raw material preparation: The molar ratio of nickel, cobalt, and manganese in the nickel-cobalt-manganese mixed salt solution is 8:1:1, and the total metal ion concentration is 2.0 mol / L; the precipitant is a 6 mol / L NaOH solution; the complexing agent is an 8 mol / L ammonia solution; the grain boundary slow-release layer additive is ammonium dihydrogen phosphate (NH4H2PO4, analytical grade), 100 g of which is weighed and dissolved in 100 L of deionized water, and the pH is adjusted to 7.2 with ammonia to prepare the additive solution for later use.

[0053] Before the reaction begins, a base solution is prepared in the reactor, maintaining the system temperature at 55 ℃, the free ammonia concentration at 0.25 mol / L, and the pH at 11.4. During the reaction, a nickel-cobalt-manganese mixed salt solution, ammonia water, and liquid alkali are simultaneously added to the reactor in parallel flow, and a nitrogen protective atmosphere is introduced. The stirring speed is controlled at 300 rpm. When the particle size D50 in the reaction system grows to 9 μm (i.e., 60% of the target particle size of 15 μm), the above-mentioned NH4H2PO4 additive solution is injected in a pulse manner: 10 mL / m is injected into the reactor each time using a metering pump. 3 The additive solution for the slurry was injected 12 minutes apart, for a total of 5 consecutive injections.

[0054] Continue the reaction until the particle size D50 reaches 10.5 μm (i.e., 70% of the target particle size), then perform the first annealing treatment: stop all feed, reduce the stirring speed to 150 rpm, fine-tune the pH of the system to 11.0 with pure water, and stop adding ammonia water at the same time, allowing the free ammonia concentration to drop naturally to about 0.18 mol / L, and maintain this for 20 min. During the annealing period, samples are taken every 5 min for testing, and there is no significant change in particle size. After the annealing is completed, resume the feed, and adjust the pH back to 11.4 and the free ammonia concentration back to 0.25 mol / L.

[0055] Continue the reaction until the particle size D50 reaches 13.5 μm (i.e. 90% of the target particle size), then perform a second annealing treatment: stop feeding, reduce the stirring speed to 150 rpm, adjust the pH to 10.9, reduce the free ammonia concentration to 0.16 mol / L, maintain for 15 min, resume feeding after annealing, and continue the reaction until the particle size D50 grows to 15.0±0.5 μm, then stop feeding.

[0056] The obtained slurry is transferred to an aging reactor for aging. After aging, it is washed, dehydrated, and dried. Then, it is mixed, sieved, demagnetized, and packaged to obtain the ternary cathode precursor product. Figure 2 As shown.

[0057] The aforementioned precursor was mixed with LiOH·H2O at a lithium to metal molar ratio of 1.05:1, and sintered in a roller kiln under an oxygen atmosphere (O2 ≥ 99.5%). The sintering process was as follows: the temperature was increased to 500 °C at a heating rate of 3 °C / min and held for 5 h, then increased to 780 °C at a heating rate of 5 °C / min and held for 12 h. After furnace cooling, the cathode material was obtained. ICP-OES analysis of the sintered cathode material showed that the residual phosphorus content was 63 ppm.

[0058] Example 2 This embodiment provides a method for preparing an NCM622 ternary cathode precursor with a D50 of 12 μm using a tetraethyl orthosilicate system combined with water vapor-assisted volatilization, including the following steps: Raw material preparation: The molar ratio of nickel, cobalt, and manganese in the nickel-cobalt-manganese mixed salt solution was 6:2:2, and the total metal ion concentration was 1.8 mol / L. Tetraethyl orthosilicate (TEOS, purity ≥99%) was used as the grain boundary slow-release layer additive. It was mixed with anhydrous ethanol at a volume ratio of 1:3, and deionized water (molar ratio of water to TEOS was 4:1) was slowly added dropwise at 25 ℃ and pH≈4.5. After stirring and hydrolysis for 2 h, SiO2 sol with a particle size of 3-5 nm was obtained.

[0059] Before the reaction began, a base solution was prepared in the reactor, and the system temperature was controlled at 60 ℃, pH at 11.3, free ammonia concentration at 0.28 mol / L, and stirring speed at 400 rpm. When the particle size D50 in the reaction system grew to 7.2 μm (i.e., 60% of the target particle size of 12 μm), the above-mentioned SiO2 sol was injected in a pulse manner, with each injection volume being 1.5 L / m. 3 The slurry was injected 10 minutes apart, for a total of 4 injections.

[0060] When the particle size D50 reaches 8.5 μm (approximately 71% of the target particle size), the first annealing is performed: all feed is paused, the stirring speed is reduced to 160 rpm, the pH is adjusted to 11.1, and the free ammonia concentration is reduced to 0.19 mol / L, and this is maintained for 20 min; samples are taken every 5 min during annealing, and no significant change in particle size is observed; after annealing, the feed is resumed, and the pH is adjusted back to 11.3 and the free ammonia concentration is adjusted back to 0.28 mol / L.

[0061] When the particle size D50 reaches 11 μm (approximately 92% of the target particle size), a second annealing is performed. The pH is adjusted to 10.8, and the free ammonia concentration is reduced to 0.15 mol / L. This is maintained for 15 min. Feeding is then paused, the stirring speed is reduced to 150 rpm, the pH is adjusted to 10.9, and the free ammonia concentration is reduced to 0.16 mol / L. This is maintained for 15 min. After annealing, feeding is resumed, and the reaction continues until the particle size D50 grows to 15.0 ± 0.5 μm, at which point feeding is paused.

[0062] The obtained slurry is transferred to an aging reactor for aging. After aging, it is washed, dehydrated, dried, mixed, sieved, demagnetized, and packaged to obtain the ternary cathode precursor product.

[0063] The aforementioned precursor was mixed with LiOH·H2O at a lithium to metal molar ratio of 1.03:1, and sintered in an experimental tube furnace. The heating program was as follows: the temperature was increased to 550 °C at 5 °C / min, then the gas was switched to N2 carrying water vapor (N2 was passed into an 80 °C constant-temperature water bath at 0.5 L / min to carry out water vapor with a relative humidity of about 5%), and held for 2 h; then the water vapor was turned off, and pure O2 was used, and the temperature was increased to 800 °C at 5 °C / min and held for 10 h. After furnace cooling, the cathode material was obtained. ICP-OES analysis showed that the residual silicon content in the obtained cathode material was only 5 ppm, reaching a level of virtually no residue.

[0064] Example 3 This embodiment provides a method for preparing an NCM85 ternary cathode precursor with a D50 of 16 μm using a diammonium hydrogen phosphate and sodium silicate composite slip layer system. The conditions and steps are the same as in Example 1, with the only difference being: Raw material preparation: The molar ratio of nickel, cobalt, and manganese in the nickel-cobalt-manganese mixed salt solution is 8.5:1:0.5, and the total metal ion concentration is 2.2 mol / L. Before the reaction begins, a base solution is prepared in the reaction vessel, and the system temperature is controlled at 55 ℃, the pH value is 11.5, the free ammonia concentration is 0.25 mol / L, and the stirring speed is 250 rpm.

[0065] The grain boundary slow-release layer additive was added in two sequential steps: First, when the particle size D50 in the reaction system grew to 10 μm (approximately 62% of the target particle size of 16 μm), diammonium hydrogen phosphate solution (concentration 0.8 g / L, pH 7.0) was added in a pulse manner, with each injection volume being 1.0 L / m³ of slurry, and an interval of 12 min between adjacent injections, for a total of 3 injections; then, when the particle size D50 grew to 12.5 μm (approximately 78% of the target particle size), sodium silicate solution (Na2SiO3·9H2O, prepared as a 0.3 g / L aqueous solution) was added in a pulse manner, with each injection volume being 1.0 L / m³ of slurry, and an interval of 15 min between adjacent injections, for a total of 3 injections. The annealing process was as follows: First annealing was performed when the particle size D50 reached 11.5 μm (approximately 72% of the target particle size), with the stirring speed reduced to 130 rpm, pH adjusted to 11.0, and free ammonia concentration reduced to 0.17 mol / L, held for 20 min. Second annealing was performed when the particle size D50 reached 14.5 μm (approximately 91% of the target particle size), with the pH adjusted to 10.8, and free ammonia concentration reduced to 0.14 mol / L, held for 15 min. Post-treatment was the same as in Example 1, yielding the ternary cathode precursor product.

[0066] The preparation method of the cathode material is the same as in Example 1. The difference is that no additional water vapor is introduced during the sintering process in this example, and the silicate portion is converted into lithium silicate residue. According to ICP-OES detection, the residual silicon content is about 30 ppm.

[0067] Comparative Example 1 This comparative example provides a method for preparing a ternary cathode precursor. The co-precipitation reaction is the same as in Example 1, but no grain boundary slow-release layer additive is added, and in-situ stress annealing is not performed. The reaction continues until D50 = 15 μm and then stops. Post-processing is the same as in Example 1, yielding the ternary cathode precursor, as shown below. Figure 3 As shown.

[0068] The above-mentioned precursor was mixed with a lithium source and sintered. The preparation method of the cathode material was the same as in Example 1.

[0069] Comparative Example 2 This comparative example provides a method for preparing a ternary cathode precursor. The co-precipitation reaction is the same as in Example 1, but only ammonium dihydrogen phosphate grain boundary slow-release layer additive is added throughout the process, and in-situ stress annealing is not performed. The reaction is stopped after D50 = 15 μm. The post-processing is the same as in Example 1, and the ternary cathode precursor is obtained.

[0070] The above-mentioned precursor was mixed with a lithium source and sintered. The preparation method of the cathode material was the same as in Example 1.

[0071] Comparative Example 3 This comparative example provides a method for preparing a ternary cathode precursor. The coprecipitation reaction is the same as in Example 1, with the addition of an ammonium dihydrogen phosphate grain boundary slow-release layer additive. However, only the final in-situ stress annealing is performed, omitting the first annealing. The reaction continues until D50 = 15 μm and then stops. The post-processing is the same as in Example 1, yielding the ternary cathode precursor.

[0072] The above-mentioned precursor was mixed with a lithium source and sintered. The preparation method of the cathode material was the same as in Example 1.

[0073] Comparative Example 4 This comparative example provides a method for preparing a ternary cathode precursor. The co-precipitation reaction is the same as in Example 1, but no grain boundary slow-release layer additive is added throughout the process; only in-situ stress annealing is performed. The reaction is continued until D50 = 15 μm and then stopped. The post-processing is the same as in Example 1, and the ternary cathode precursor is obtained.

[0074] The above-mentioned precursor was mixed with a lithium source and sintered. The preparation method of the cathode material was the same as in Example 1.

[0075] Experimental Example 1 The precursors and cathode materials prepared in each embodiment and comparative example were subjected to performance tests. The method for calculating the precursor cracking rate was as follows: 100 g of each precursor product obtained from each embodiment and comparative example was taken, dispersed in deionized water to prepare a slurry, and allowed to stand for 12 h under low stirring conditions. After drying and sieving, the particle morphology was observed using a scanning electron microscope (SEM), and the percentage of cracked particles in the total count was counted. Each sample group had at least 500 cracked particles. The method for testing the cycle performance of the cathode materials was as follows: the cathode materials obtained from each embodiment and comparative example were assembled into CR2032 coin cells, and charge-discharge cycle tests were conducted at 1C / 1C rate within a voltage range of 3.0-4.3 V. The capacity retention rate after 500 cycles was recorded. The test results are shown in Table 1.

[0076]

[0077] As shown in Table 1, the cracking rate of the large-particle-size ternary precursors prepared in each example was significantly lower than that of all comparative examples. Among them, Example 3 had the lowest cracking rate (2.8%), corresponding to the highest capacity retention rate after 500 weeks (91.5%); the cracking rates of Examples 1-3 were 2.8%-5.6%, and the capacity retention rates were 86.3%-91.5%; while the cracking rate of Comparative Example 1 (conventional process, no additives, no annealing) was as high as 15.2%, and the capacity retention rate was only 79.1%. A comparison of Example 1 with Comparative Examples 2, 3, and 4 shows that when only a grain boundary slip layer is added without in-situ annealing (Comparative Example 2), the cracking rate of the precursor is 8.5%, significantly higher than the 2.8-5.6% of the present invention. When only in-situ annealing is used without adding a grain boundary slip layer (Comparative Example 4), the cracking rate is 9.8%, still significantly higher than the solution of the present invention. When only one annealing is performed in the final stage instead of segmented annealing (Comparative Example 3), the cracking rate is 7.0%, showing some performance improvement, but still significantly less than the synergistic effect of two segmented annealings in the present invention. This fully verifies that relying on a single method cannot achieve the desired effect; only by combining a chemically constructed grain boundary slip layer with physically implemented segmented in-situ annealing can a significant synergistic effect be achieved.

[0078] In summary, the combined process of "grain boundary slip layer + in-situ annealing" proposed in this invention can significantly suppress spontaneous cracking of large-particle-size ternary precursors, improve the structural integrity of precursor particles, and reduce the cracking rate from 15.2% in the traditional process to 2.8%-5.6%. Ultimately, it can increase the 500-cycle capacity retention rate of the cathode material from 79.1% to 86.3%-91.5%, which fully demonstrates the key influence of precursor structural integrity on the cycle stability of cathode materials.

[0079] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a large-particle-size ternary cathode precursor that suppresses spontaneous cracking, characterized in that, Includes the following steps: A nickel-cobalt-manganese mixed salt solution, a precipitant, and a complexing agent are stirred and mixed to carry out a co-precipitation reaction. When the particle size D50 of the particles in the reaction system grows to 60%-70% of the target particle size D, a grain boundary slow-release layer additive is added to the system in a pulsed manner to perform in-situ coating modification on the particle surface. The reaction continues until the particle size D50 of the coated particles grows to 70%-80% of the target particle size D, at which point the feed is stopped and the first annealing is performed. After annealing, the feed is continued. The reaction continues until the particle size D50 grows to 90%-95% of the target particle size D, at which point the feed is stopped and the second annealing is performed. After annealing, the feed is continued. The reaction continues until the particle size reaches the target particle size D. The resulting slurry is aged, washed, dried, mixed, sieved, demagnetized, and packaged to obtain a ternary cathode precursor.

2. The preparation method according to claim 1, characterized in that, The total metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 1.5 mol / L - 2.5 mol / L; And / or, the precipitant is a sodium hydroxide solution with a concentration of 4 mol / L - 12 mol / L; And / or, the complexing agent is an aqueous ammonia solution with a concentration of 4 mol / L - 12 mol / L; And / or, the target particle size D of the ternary cathode precursor is 10-20 μm.

3. The preparation method according to claim 1, characterized in that, The coprecipitation reaction includes at least one of the following characteristics: Feature 1: The coprecipitation reaction temperature is 40 ℃-80 ℃; Feature 2: The pH value of the coprecipitation reaction system is 9.5-12.5; Feature 3: The concentration of free ammonia in the coprecipitation reaction system is 0.1 mol / L - 0.5 mol / L; Feature 4: The stirring speed is controlled at 100 rpm - 1000 rpm during the coprecipitation reaction.

4. The preparation method according to claim 1, characterized in that, The grain boundary slow-release layer additive is selected from at least one of silicate additives or phosphate additives. And / or, the pulsed addition method is as follows: each injection of the grain boundary slow-release layer additive solution is 10 mL / m 3 -20mL / m 3 Inject 3-5 times consecutively at 10-15 minute intervals.

5. The preparation method according to claim 4, characterized in that, The grain boundary slow-release layer additive is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, tetraethyl orthosilicate, and sodium silicate.

6. The preparation method according to claim 4, characterized in that, The concentration of the phosphate additive solution is 0.2 g / L-1.0 g / L, and the pH value is 7.0-7.5; And / or, the silicate additive is a silica sol with a particle size <5 nm, or a silicate solution with a concentration of 0.2 g / L-1.0 g / L.

7. The preparation method according to claim 1, characterized in that, The annealing process takes 10-60 minutes. And / or, the reaction during the annealing process includes at least one of the following characteristics: Feature 1: The stirring speed during the reaction is 40 rpm - 800 rpm; Feature 2: The pH value of the reaction system is 8.7-12.5; Feature 3: The concentration of free ammonia in the reaction system is 0 mol / L-0.5 mol / L.

8. A ternary cathode precursor obtained by the preparation method according to any one of claims 1-7, characterized in that, The ternary cathode precursor is a secondary spherical particle of nickel cobalt manganese hydroxide, which is formed by the aggregation of primary particles. The grain boundary gaps between the primary particles are coated with a grain boundary slow-release layer in situ. The grain boundary slow-release layer is an amorphous or weakly crystalline stress slip layer with a thickness of 2 nm-10 nm.

9. A positive electrode material, characterized in that, The ternary cathode precursor prepared by any one of the preparation methods of claims 1-7 or the ternary cathode precursor of claim 8 is obtained by sintering with a lithium source.

10. The cathode material according to claim 9, characterized in that, The molar ratio of metal ions to lithium source in the ternary cathode precursor is 1:(1.00-1.08); the sintering process is as follows: pre-sintering at 400℃-600℃ for 4h-6h by heating at 2℃ / min-5℃ / min, then heating to 700℃-850℃ and holding for 10h-15h, and then cooling to room temperature in the furnace.